Development of Sanak Belajar Mobile Learning Media on Atomic Structure Material - Ridwansyah, Muhammad; Akbar, Muhammad; Nurhadi, Mukhamad; Kusumaningtyas, Pintaka; Rahmadani, Agung (Pendidikan Kimia FKIP Universitas Jambi, 2026)
Mobile learning is increasingly important to support flexible and adaptive learning. This study aims to develop a mobile learning-based Sanak Belajar learning media on atomic structure material, and test its validity, practicality, and effectiveness. The method used is Research and Development (R&D) with a modified ADDIE model at the Analysis, Design, Development, and Implementation stages. The research subjects were purposively selected X-grade students of SMA Negeri 1 Loa Janan. The validation results by experts showed a very high level of validity (score >90%). Practicality based on teacher and student questionnaires is also very high, amounting to 97.92% and 79.81% respectively. The effectiveness of the media is seen from the N-Gain value of 0.64 (medium category) and effect size of 3.39 (very high impact). Thus, Sanak Belajar is declared valid, practical, and effective for use in learning chemistry on atomic structure material, and has the potential to be further developed with more interactive technology